2019
DOI: 10.1371/journal.pone.0219577
|View full text |Cite
|
Sign up to set email alerts
|

Postablation assessment of hepatocellular carcinoma using dual-energy CT: Comparison of half versus standard iodine contrast medium

Abstract: This retrospective study was aimed to evaluate the reduced iodine load on image quality and diagnostic performance in multiphasic hepatic CT using a novel monoenergetic reconstruction algorithm (nMERA) in assessment of local tumor progression after radiofrequency ablation (RFA) of hepatocellular carcinoma (HCC). Ninety patients who underwent CT 1 month after RFA of HCC. Forty-five patients had multiphasic hepatic dual-energy CT with a half-reduced contrast medium (HRCM) of 277.5 mg I/kg. The nMERA (40–70-keV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…DECT not only has better diagnostic performance but also presents surprising advantages compared with conventional CT, particularly in terms of contrast and radiation dose. 16,17 This is because it allows for the reconstruction of virtual monoenergetic imaging by combining two different datasets (obtained by low-and high-energy tubes).…”
Section: Contrast and Radiation Reductionmentioning
confidence: 99%
“…DECT not only has better diagnostic performance but also presents surprising advantages compared with conventional CT, particularly in terms of contrast and radiation dose. 16,17 This is because it allows for the reconstruction of virtual monoenergetic imaging by combining two different datasets (obtained by low-and high-energy tubes).…”
Section: Contrast and Radiation Reductionmentioning
confidence: 99%
“…In previous studies (8)(9)(10)(11), dual-energy CT (DECT) scanning has been proven to be effective and quantitative in evaluating the prognosis of HCC patients after treatment. At the same time, other relevant studies have shown that extracellular volume fraction (fECV) based on the iodine density of DECT scanning can quantify the liver extracellular volume and early identify patients with high risk for developing liver-related adverse events (12-15).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most aggressive and lethal cancer among different cancers, with five‐year overall survival of approximately 10 to 15 %. It is now regarded as the third most common cause of cancer‐related death [1,2] . Considerable progress has been made in diagnosis, surgery, and treatment over the past few decades for the HCC treatment.…”
Section: Introductionmentioning
confidence: 99%